From Collegiality to Managerialism in Lithuanian Higher Education - Želvys, Rimantas; Leišytė, Liudvika; Pekşen, Sude; Bružienė, Rūta; Rose, Anna-Lena (Acta Paedagogica Vilnensia, 2021)
In this paper we focus on the development and academics’ perceptions of managerialism in Lithuanian higher education (HE). We systematically investigate historical changes in HE governance and policies in Lithuania and conduct an analysis of data collected through the APIKS Lithuania project survey of academics at Lithuanian public universities (N=389). We find that Lithuanian HE policies shifted to a rather market-oriented paradigm. The survey results reveal that the majority of respondents perceive their university as highly managerial, which points out to high managerialism in practice in line with the policies. Based on our key findings, we discuss theoretical and practical implications.